Analisis Sarana Prasarana Penggunaan Laboratorium Biologi terhadap Sikap Ilmiah Siswa - Zainuddin Rambe; Hasmi Syahputra Harahap (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Facilities and infrastructure in the use of biology laboratories towards scientific attitudes in practical learning in this case make it easier for students to study biology, and can carry out practicums and observations in biology learning which are studied using practical facilities and infrastructure in the learning process. This research aims to be able to see and find out the infrastructure and facilities for using biology laboratories on the scientific attitudes of students at SMA Negeri 2 Rantau Utara. This type of research is descriptive qualitative. The population in this study were students and teachers at SMA Negeri 2 Rantau Utara. The sample population was 50 students and 4 teachers at SMA Negeri 2 Rantau Utara using purposive sampling technique. Data collection techniques were carried out by administering questionnaires and interviews. As for the results of the research regarding the use of biology laboratories on the scientific attitudes of students at SMA Negeri 2 Rantau Utara, results were obtained for each indicator of laboratory facilities and infrastructure, namely reports and evaluations, implementation time in practicums, preparation of equipment and materials, and implementation of laboratory conditions. Meanwhile, the indicators for scientific attitude are responsibility, honesty, enthusiasm and thoroughness. In this case, the infrastructure for using the biology laboratory for students' scientific attitude is something that supports and supports the learning process to be optimal and better.